simplify the square foor of 49 times x to the third time y to the sixth times the absolute value of z squared
if this is x squared -6x+6=0 then -6=b, a=1, c=6 6+ square root of -6 squared-4(6x1) - 6+ square root of (36-24) - 6+ square root of 12 - 6+ square root of 4 x square root of 3 - 6 + (2x square root of 3) - that is all divided by 2 multiplied by a meaning it is divided by 2. so x= 6 + or - (2 square root 3) divided by 2 srry steps are jmbled -
- ln ((x^2)-4)
It is negative one divided by 4 multiplied by x to the power of 1.5 -1/(4(x^1.5))
4x-x^2 \ 2-square root 2 multiply 2+squre root x\ 2+squreroot x = 4x-x^2 (2+squre root x) \ 4_x = x(4-x) (2+squre root x) \ 4-x we will cancel the (4-x) so it will be x(2+squre root x) = (0) (2+squre root 0) =0
simplify the square foor of 49 times x to the third time y to the sixth times the absolute value of z squared
The square root of x12 is x6 .
3
300*square root of 3 + 300*square root of 6 = 1254.462165
x=y
replace square root o x with t.
20 is 5x4 so we can simplify it like this: ____ ______ / = / \/ 20 \/ 5 x 4 Also note that: ____ / = 2 \/ 4 So... ____ ____ / = / \/ 20 2 \/ 5
The fraction must be rationalized. Since it is the square root of x in the denominator, you are going to multiply the numerator and denominator by the square root of x. For simplicity of the problem, root will take the place of the symbol for square root: root(3y)/root(x) root(3y)*root(x)/root(x)*root(x) root(3xy)/x The simplified answer is going to be the square root of 3xy divided by x. Hope that helped.
The square root of 60 is also equal to the square root of 15x4 the square root of 4 is 2, and 15 is not a perfect square, so the answer is (square root of 15) x 2
To simplify the square root of 5 times the square root of 6, you can multiply the two square roots together. This gives you the square root of (5*6), which simplifies to the square root of 30. Therefore, the simplified answer is the square root of 30.
4
7 x 2½